Clinical and Genetic Spectrum of a Large Cohort of Patients With Leukocyte Adhesion Deficiency Type 1 and 3: A Multicentric Study From India - Kambli, Priyanka Madhav; Bargir, Umair Ahmed; Yadav, Reetika Malik; Gupta, Maya Ravishankar; Dalvi, Aparna Dhondi; Hule, Gouri; Kelkar, Madhura; Sawant-Desai, Sneha; Setia, Priyanka; Jodhawat, Neha; Nambiar, Nayana; Dhawale, Amruta; et al. (Frontiers in Immunology, 2020)
Leukocyte adhesion deficiency (LAD) syndrome is a group of inborn errors of immunity characterized by a defect in the cascade of the activation and adhesion leading to the failure of leukocyte to migrate to the site of tissue injury. Three different types of LAD have been described. The most common subtype is LAD1 caused due to defects in the ITG2 gene. LAD type 2 (LAD2) is caused by mutation in the SLC35C1 gene leading to a generalized loss of expression of fucosylated glycans on the cell surface and LAD type 3 (LAD3) is caused by mutation in the FERMT3 gene resulting in platelet function defects along with immunodeficiency. There is a paucity of data available from India on LAD syndromes. The present study is a retrospective analysis of patients with LAD collated from 28 different centers across India. For LAD-I, the diagnosis was based on clinical features and flow cytometric expression of CD18 on peripheral blood leukocytes and molecular confirmation by Sanger sequencing. For patients with LAD3 diagnosis was largely based on clinical manifestations and identification of the pathogenic mutation in the FERMT3 gene by Next-Generation Sequencing. Of the total 132 cases diagnosed with LAD, 127 were LAD1 and 5 were LAD3. The majority of our patients presented within the first three months of life with omphalitis (60%), skin and soft tissue infections (60%), delayed umbilical cord detachment (56%), otitis media (23%), and sepsis (24%). Bleeding manifestations were common in patients with LAD3. Persistent neutrophilic leukocytosis was the characteristic finding in all patients. 35 novel mutations were detected in the ITGβ2 gene, and 4 novel mutations were detected in the FERMT3 gene. The study thus presents one of the largest cohorts of patients from India with LAD, focusing on clinical features, immunological characteristics, and molecular spectrum.